(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
We investigated the effect of Punica granatum peel aqueous extract (PGE), on pulmonary inflammation and alveolar degradation induced by intratracheal administration of Elastase in Sprague Dawley rats. Lung inflammation was induced in rats by intratracheal instillation of Elastase. On day 1 and 2, animals received an intraperitoneal injection of PGE (200 mg/mL), three hours later, they were intratracheally instilled with 25U/kg pancreatic porcine Elastase. Animals were sacrificed 7 days later. Bronchoalveolar lavage (BAL) were collected and cellularity, histology and mRNA expression of Monocyte chemotactic protein 1(MCP-1), Tumor Necrosis Factor-Alpha (TNF-α), Interleukin 6 (IL-6), and Matrix Metalloproteinase-2 (MMP-2) were studied. In addition, activity of TNF- α, IL-6 and MCP-1 on BAL were also analyzed byELISA Kit. Elastase administration increased: BAL cellularity, neutrophils recruitment and BAL MCP1, IL-6 expressions. It also increased lung TNF-α, MCP-1, MMP-2 expressions, platelets recruitment, histological parameters at 7th day of elastase treatment. Intraperitoneal injection of 200 mg/kg of PGE reduced, significantly, BAL cellularity, and neutrophils recruitment. However, in animal treated with PGE, MCP-1, MMP-2 and IL-6 on day 7, were similar to the Sham group. Treatment with PGE (200 mg/kg) also significantly reduced lung TNF-α, and MCP-1 expression. This study reveals that PGE Punica granatum protects against elastase lung inflammation and alveolar degradation induced in rats.